AI Literacy and Adaptive Learning in Moroccan Education: Advancing Critical Thinking and Personalized Learning - Ismaili Yassine (Research on Education and Media)
This research examines how artificial intelligence (AI) can be effectively integrated into education. It focuses on the skills and strategies that students and educators need to be successful. The study takes a qualitative approach. It includes discussions with students and faculty at a Moroccan University of Interdisciplinary Studies and a review of the relevant literature. The findings show that AI has great potential to enhance learning and critical thinking. However, there is a clear need for structured training and strong institutional support to build AI literacy. The study suggests that educational institutions should take a comprehensive approach to integrating AI. This includes creating training programs, integrating AI into the curriculum, and encouraging collaboration on AI-related projects. These steps can help prepare students for a future in which AI plays an important role in their careers. This research adds to the ongoing conversation about AI in education. It also offers practical ideas for improving teaching and learning with technology.